Investigation the properties of paint coatings modified by carbon nanostructures - Zelensky, O. I.; Shmalko, V. М.; Distanov, V. B. (НТУ "ХПІ", 2010)
The article presents the results testing the possibility of applying structured solvents using nanomodifiers for the production of water-based paints and pentaphthal. As nanomodifiers used suspensions of carbon nanostructures obtained from the waste by-product coke production – coke dust recovered from plants dust-free coke.

У статті наводяться результати випробувань можливості застосування структурованих розчинників з використанням наномодіфікаторов для виробництва водоемульсійних і пентафталевих лако-фарбових покриттів. В якості наномодіфікаторов застосовувалися суспензії вуглецевих наноструктур, отримані з відходів коксохімічного виробництва - коксового пилу, який уловлюється в установках беспилової видачі коксу.
Keywords: CNS; multi-walled carbon; nanomodifiers; waterborne paint; dust free pushing; DFP